The Effect Of Preoperative Embolization On Surgical Outcomes Of Medial Sphenoid Wing Meningioma : A Comparative Study - Paudel, Kumar; Adhikari, Sudeshana; Khadka, Namrata; Bhattarai, Sushil Mohan; Rajbhandari, Binod; Aryal, Sameer; Jha, Binit; Shrestha, Rajendra; Jha, Rajiv (Nepal Journal of Neuroscience, 2024)
Objective: This study aims to compare the outcomes of patient undergoing surgery of medial sphenoid wing meningioma with or without preoperative embolization.Methods: This prospective single centre observational study was performed over 2 years (1st August 2021 to 30th September 2023) at National Neurosurgical Referral Centre, Bir hospital. Patients were allocated to surgery with or without preoperative embolization.Results: Among the 20 patients operated , 17 were female and 3 were male .The mean age of presentation was 48.2±10.8 years. The presenting symptoms were headache (50%), Visual disturbances (19%), proptosis (9%), seizure (13%), dizziness (22%). Of the 20 patients in this study ,10 underwent prior embolization of feeding vessel followed by surgery while 10 underwent upfront craniotomy and excision of mass. The tumor size at presentation was 4 cm in 15%. The mean operative time was short in embolized group [187min vs 234min, (p=0.047)]. The mean blood loss was less in embolized group 295 ml vs 436 ml p =0.005). Preoperative embolization had higher rate of  gross total tumor resection (100% vs 60%). The embolization group had shorter overall  hospital stay (5.6 days vs 8.6 days ). There is no mortality. However increased morbidity observed in non-embolized group.Conclusions : The preoperative endovascular embolization  of meningiomas is safe option for medial sphenoid wing meningiomas. The extent of tumor resection ,intraoperative blood loss and hospital stay was better in embolization group compared to non-embolization group.